Minor Biomass Particle Size for an Efficient Cellulose Accessibility and Enzymatic Hydrolysis - Fernandes, Érika S. [UNESP]; Bueno, Danilo [UNESP]; Pagnocca, Fernando C. [UNESP]; Brienzo, Michel [UNESP] (Wiley, 2020)
Sugarcane bagasse is a recalcitrance lignocellulosic material with difficult to structure disorganize and it has low cellulose accessibility, negatively influencing the enzymatic saccharification. This study identified the minor particle size that resulted in the efficient diluted acid pretreatment (10 % m/m, 121 °C/30 min) of sugarcane bagasse and a more recalcitrant material, that is external fraction (2 to 3 mm from the extremity, containing epidermis). Particle sizes were obtained by sieving sugarcane bagasse at 16 (1 mm), 24 (0.710 mm), 35 (0.425 mm), 60 (0.250 mm) and <60 mesh (<0.250 mm) on a sieve agitator. The decrease of the particle sizes led to an increase of cellulose accessibility. Both of the samples showed high accessibility after the pretreatment due to the particle size decrease. Accordingly, there was a better enzyme action, what increased the glucose yield with samples lower than 0.425 mm (35 mesh).
Keywords: acid pretreatment; cellulose; lignocellulosic material; recalcitrance; sugarcane